2000
DOI: 10.1016/s0014-2999(00)00002-9
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation and inhibition of neuronal α4β4 nicotinic acetylcholine receptors by choline

Abstract: The effects of choline on a4b4 nicotinic acetylcholine receptors, expressed in Xenopus oocytes, were investigated using the two-microelectrode voltage clamp technique. Particular attention was paid to the interaction between the effects of acetylcholine and choline. Choline was a low-affinity agonist of a4b4 receptors with an efficacy of 10% as compared to acetylcholine. Responses evoked by 1 mM acetylcholine were potentiated by low concentrations of choline and inhibited by ) 10 mM choline, resulting in a bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 17 publications
(21 reference statements)
3
22
0
Order By: Relevance
“…Potentiation of the response was not limited to imidacloprid, but was also seen for clothianidin. Similar actions have also been observed for d-tubocurarine, 17) atropine 18) and choline, 19) and these observations have been interpreted in terms of an equilibrium two-site receptor occupation model. 19,20) According to this model, sequential occupation of the two agonist binding sites by two different agonists greatly enhances the probability of opening the nAChR channel.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Potentiation of the response was not limited to imidacloprid, but was also seen for clothianidin. Similar actions have also been observed for d-tubocurarine, 17) atropine 18) and choline, 19) and these observations have been interpreted in terms of an equilibrium two-site receptor occupation model. 19,20) According to this model, sequential occupation of the two agonist binding sites by two different agonists greatly enhances the probability of opening the nAChR channel.…”
Section: Discussionsupporting
confidence: 71%
“…Similar actions have also been observed for d-tubocurarine, 17) atropine 18) and choline, 19) and these observations have been interpreted in terms of an equilibrium two-site receptor occupation model. 19,20) According to this model, sequential occupation of the two agonist binding sites by two different agonists greatly enhances the probability of opening the nAChR channel. Potentiation by imidacloprid and clothianidin of the ACh-induced response may also be accounted for in a similar fashion, because the action was reduced by increasing the ACh concentration (Figs.…”
Section: Discussionsupporting
confidence: 71%
“…Micromolar concentrations of choline, a selective endogenous agonist of α7 nAChRs (Alkondon et al, 1997;Papke et al, 1996), have been shown to activate α7 nAChRs or reduce the responsiveness of α7 nAChRs to ACh (Uteshev et al, 2003;Alkondon and Albuquerque, 2006). Choline however, has been reported to inhibit β4* nAChRs expressed in Xenopus oocytes (Zwart and Vijverberg, 2000;Gonzalez-Rubio et al, 2006). Therefore, the effects of choline on pre-synaptic and somatic/dendritic nAChRs would be expected to be opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Although other PAMs exist, the current information does not permit to separate them into type I or type II modulators yet. For instance, 17b-estradiol (Paradiso et al, 2001;reviewed in Arias and Bouzat, 2006), the ACh metabolite choline (Zwart and Vijverberg, 2000), and peptides derived from the C-terminus of acetylcholinesterase Zbarsky et al, 2004) and from the N-terminal region of calcitonin gene related peptide (CGRP) (i.e., CGRP1-6, CGRP1-5, and CGRP1-4) (Di Angelantonio et al, 2002.…”
Section: A Positive Allosteric Modulatorsmentioning
confidence: 99%